Steely Dan FAQ: All That's Left to Know About This Elusive Band - Robustelli, Anthony (Rowman & Littlefield Publishers, 2017)
Despite Steely Dan's popularity, its ability to cultivate an ever-growing base of avid and loyal fans, and its chart positions, relatively little has been written about the group. Steely Dan FAQ clears up some of the many misconceptions about the band and sheds new light on the genius behind the songwriting of Donald Fagan and Walter Becker, the perfection of their productions, and the myriad musicians who have played a role in creating the distinctive Steely Dan sound. Steely Dan FAQ takes us through five decades of cryptic lyrics, sophisticated music, elusive interviews, dramatic interludes, and misconstrued sentiments. The band has sold more than 40 million albums worldwide, was inducted into the Rock and Roll Hall of Fame, and has had the majority of its albums certified platinum or double platinum in the U.S., yet the story has not been fully told. Within these pages readers will gain insight into the influences, musicians, situations, and complications that created one of the most distinctive bands in the history of rock and roll.